2014
DOI: 10.1039/c4cp01667j
|View full text |Cite
|
Sign up to set email alerts
|

Excited states of multiply-charged anions probed by photoelectron imaging: riding the repulsive Coulomb barrier

Abstract: Publisher's copyright statement:Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 91 publications
2
45
0
Order By: Relevance
“…While our initial work focused on photodissociation, in principle, this method may be applied to any laser-driven system that can be measured using an imaging technique. Some interesting possibilities include rescattering electrons, 62,63 nanoplasmas, 64 nanodroplets, 65 laserinduced molecular motions 66 and excitations, 67 and finally the possibility of one day using laser-induced electron diffraction of molecules 62,68 or photoelectron tomography 69 as control targets. Given the general applicability of 3D-VMI feedback and the context-rich information that can be gleaned from these images, there are undoubtedly additional directions that might be explored, especially in more complex systems.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…While our initial work focused on photodissociation, in principle, this method may be applied to any laser-driven system that can be measured using an imaging technique. Some interesting possibilities include rescattering electrons, 62,63 nanoplasmas, 64 nanodroplets, 65 laserinduced molecular motions 66 and excitations, 67 and finally the possibility of one day using laser-induced electron diffraction of molecules 62,68 or photoelectron tomography 69 as control targets. Given the general applicability of 3D-VMI feedback and the context-rich information that can be gleaned from these images, there are undoubtedly additional directions that might be explored, especially in more complex systems.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…[75][76][77][78][79][80] The coupling of ESI with PES allowed MCAs to be spectroscopically characterized for the first time. [4][5][6][32][33][34][35][36][37][38][39][40] When an electron is detached from a MCA, it experiences a short-range attraction by the nuclei and a long-range repulsion from the negatively charged residual ion, resulting in the socalled RCB (Fig. 2(a)).…”
Section: Photoelectron Imaging Of Multiply-charged Anions: the Imentioning
confidence: 99%
“…A number of reviews and perspectives on the PES of MCAs have appeared; [32][33][34][35][36] and this perspective focuses on more recent advances. The article is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…We have also performed our experiments under "colder" conditions which revealed that the rotational dephasing indeed slows down to t min ~ 3 ps, corresponding to an internal temperature of T ~ 300 K (see supporting information). 38,39 A full analysis of the rotational dephasing would allow an accurate determination of the rotational constants of a molecular system from τ r , 37 however, as this requires an accurate determination of the internal temperature, such an analysis is beyond the scope of this study. In TR-FA, τ r can be related to the local viscosity of the solvent, which is clearly not appropriate for a gas-phase experiment.…”
mentioning
confidence: 99%